The Effect Of Booklet Media On Mothers' Knowledge About Pregnant Women's Classes - Arum, Melati Puspita (Jurusan Kebidanan Poltekkes Kemenkes Sorong, 2024)
One effort to reduce this is through pregnancy class activities. Efforts made to support mothers' knowledge about pregnancy classes are by providing education using health promotion media. Booklets are printed media in the form of small books that contain pictures and writing. Booklet media can attract many people in a short time because the presentation of booklets is more flexible so that it can be used as a communication medium in various groups of society (Krisdianto, 2023). The aim of the research is to determine the effect of booklet media on mothers' knowledge about pregnancy classes at the Amban Community Health Center. Research method: This research is experimental research with the design used is quasi-experimental. This research was carried out in March-April 2024. The population of this study was pregnant women. The number of samples in the study was 14 people. The research results used univariate and bivariate analysis using the Paired test. The pre-test and post-test values ​​with p-value=0.001 (p-value <0.05). The conclusion of this research is that there is an influence of booklet media on mothers' knowledge about classes for pregnant women.